2019
DOI: 10.1186/s12906-019-2711-5
|View full text |Cite
|
Sign up to set email alerts
|

Bryophyllum pinnatum enhances the inhibitory effect of atosiban and nifedipine on human myometrial contractility: an in vitro study

Abstract: BackgroundThe herbal medicine Bryophyllum pinnatum has been used as a tocolytic agent in anthroposophic medicine and, recently, in conventional settings alone or as an add-on medication with tocolytic agents such as atosiban or nifedipine. We wanted to compare the inhibitory effect of atosiban and nifedipine on human myometrial contractility in vitro in the absence and in the presence of B. pinnatum press juice (BPJ).MethodsMyometrium biopsies were collected during elective Caesarean sections. Myometrial strip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…However, when combined with atosiban the TI of mundulone dramatically improved to a favorable TI = 10, and therefore, shows potential for combination with current tocolytics. To this end, at least one other study reported improved inhibition of uterine contractility when another flavonoid containing plant extract from Bryophyllum pinnatum was combined with atosiban or nifedipine [18]. In our study, the ex vivo tocolytic efficacy and potency of mundulone in combination with atosiban significantly improved using term-pregnant mouse and human myometrial tissue.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, when combined with atosiban the TI of mundulone dramatically improved to a favorable TI = 10, and therefore, shows potential for combination with current tocolytics. To this end, at least one other study reported improved inhibition of uterine contractility when another flavonoid containing plant extract from Bryophyllum pinnatum was combined with atosiban or nifedipine [18]. In our study, the ex vivo tocolytic efficacy and potency of mundulone in combination with atosiban significantly improved using term-pregnant mouse and human myometrial tissue.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, a recent review on natural products for tocolysis found that most plant extracts for inhibition of uterine contractions belong to flavonoid or terpene classes [16]. Interestingly, plant extracts containing flavonoids have shown tocolytic effects (J. flava, B. pinnatum, T. paniculatum), with B. pinnatum entering into a clinical trial that was, unfortunately, withdrawn early due to lack of patient enrollment [17][18][19][20][21][22]. Therefore, mundulone and MA belong to an interesting class of compounds to study for tocolytic potential.…”
Section: Introductionmentioning
confidence: 99%
“…Using the myograph model, we previously showed that BPJ concentration-dependently inhibits spontaneous myometrium contractions, affecting their peak, tension, and duration ( Fürer et al, 2016 ; Santos et al, 2019a ). Stronger effects on spontaneous contractility were observed when BPJ was combined with atosiban ( Santos et al, 2019b ). However, a comparison of findings in these models should be done with caution given that the modulation of contractility in myometrium strips is a much more complex process than what can be investigated with a cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have shown a very good tolerability of B. pinnatum preparations for this ( Plangger et al, 2006 ; Fürer et al, 2015b ; Simões-Wüst et al, 2018 ) and other indications ( Betschart et al, 2013 ; Lambrigger-Steiner et al, 2014 ). In vitro studies showed that B. pinnatum reduces the strength of human myometrium contractions ( Santos et al, 2019a ; Santos et al, 2019b ). In human myometrial cells (hTERT-C3 cell line), leaf press juice of B. pinnatum (BPJ) lowered the OT-induced increase of intracellular calcium concentrations [(Ca 2+ ) i ] ( Simões-Wüst et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…B. pinnatum is known to act on uterine contractility. In vitro research with human myometrial cells has been conducted at university centers in Switzerland since the early 2000s [3,29,30,55,56]. Several clinical studies have also evaluated the tocolytic effect of B. pinnatum in premature labor [44,45,57].…”
Section: Discussionmentioning
confidence: 99%